Infants under 3 months old with cyanosis at the emergency room: could it be gastroesophageal reflux?. Issue 4 (5th September 2013) - Epifanio, M.; Eloi, J.; Cassiano, A. S.; Pinheiro, D.; Spolidoro, J. V.
Summary The aim of this study is to describe the prevalence of gastroesophageal reflux disease (GERD) in infants under 3 months old with a history of cyanotic episodes, who were examined at the emergency room of a university hospital. This descriptive study reviews reports of esophageal pH monitoring from a pediatric gastroenterology service over a period of 5 years. The following data were collected: age, sex, pediatric as well as other specialists' evaluations, and the esophageal pH monitoring reports. This study included 67 infants with a history of cyanotic episodes, with no primary cause determined by pediatrician and pediatric specialists' evaluations, who underwent esophageal pH monitoring. The infants were 6–90 days old, 41 (61.2%) of them male. Fifty infants (74.6%) had at least one esophageal pH monitoring parameter above the normal limit. ZMD index was abnormal in 32 cases (48%) and reflux index was abnormal in 31 cases (46%). When other common causes of cyanosis have been ruled out, a significant proportion of infants presenting cyanosis have abnormal pH study, suggesting the role of GERD in cyanosis. The authors highlight that reflux index is not enough to conclude whether a pH study is normal or not. The ZMD index and the presence of episodes longer than 20 minutes are also important parameters for GERD diagnosis.